Análise faunística e nível de infestação de moscas-das-frutas (Diptera: Tephritidae) em pomar comercial de goiaba (Psidium guajava L.) em São Luis – MA - Maciel, Alba Albertina Sarmento (2011)
The objective was to study the fluctuation of fruit flies and their level of infestation in fruit orchard of guava (Psidium guajava L.) cultivar Paluma, located in the Village Maranhão (Sao Luis, Brazil). We used the period to February/2008 January/2009, plastic traps flies containing hydrolyzed protein with 500 mL/10 L water. Samples were collected fortnightly. For the level of infestation, fruits were collected during the same period, which were individualized in plastic containers with sterilized sand and kept in an incubator (temperature 25 ± 2 ° C, relative humidity 70 ± 10% and photoperiod of 12 hours) . Determined the species composition of fruit-flies, the faunal analysis of adult tephritidae and the correlation between population dynamics and climatic factors measured by the Pearson coefficient (p <0.05). The fluctuation index was estimated by the MAD (fly / trap / day) and infestation levels in pupae / kg of fruit and puparia / fruit. We collected 2901 individuals, collected in 2328 and 573 traps in fruit. The species were: Anastrepha striata, A. obliqua, Anastrepha fraterculus, Anastrepha sororcula, Anastrepha distincta, Anastrepha zenildae and Anastrepha pickeli. The species A.striata stood out as the most frequent, dominant and constant. There was a negative correlation between air temperature and the occurrence of flies, a correlation between this factor and the relative humidity and rainfall did not affect the number of trapped insects. The infestation levels were higher in August and is 231.2 pupae / kg and 26.42 pupae / fruit. High values of the index of MAD (2.9) indicate a high prevalence of flies in the orchard under study and the need for constant monitoring of this pest.